التصميم الانشائي لمبنى تجاري سكني - البشيتي, شروق; ابو عرقوب, ولاء; السويطي, وفاء (جامعة بوليتكنك فلسطين - مباني, 2020)
The idea of this project is summarized in the structural design of residential commercial building. The project is a building with a gross area equal to "10244" square meters, It consists of 12 floors: two underground basement floors which have an area of approximately 1500 square meters for each, In addition to the floor of commercial story have an area of approximately 735 square meters with ground level topped by store floor and 6 residential floors, each floor equivalent to approximately 786 square meters, and 2 roof floors. The building is reinforced concret structure and composit steel-concrete structure, the project contains the structural analysis for vertical and horizontal loads.
CD, no of pages 66 , مباني 21/2020
Keywords: التصاميم الانشائية; المباني السكنية; المباني التجارية